Das Potenzial der Kinderliteratur im Hinblick auf den frühen Fremdspracherwerb The Role of Children’s Literature in Early Language Learning - Ciepielewska-Kaczmarek, Luiza (Glottodidactica, 2012)
Children's literature is undoubtedly a very useful tool in teaching and learning foreign languages and its educational value is remarkable. Storybooks contain rich and authentic examples of the language being learned, they involve children personally and actively in the process of language learning and they address the issues relevant to children’s interests and their perception of the world. The aim of the article is to show how children's literature can be used effectively in teaching a foreign language.